2012
DOI: 10.1016/j.jcv.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A national study of individuals who handle migratory birds for evidence of avian and swine-origin influenza virus infections

Abstract: Background Persons with occupational or recreational exposure to migratory birds may be at risk for infection with highly pathogenic avian influenza and other avian influenza viruses since wild birds are the natural reservoir of influenza A. Additionally, bird handlers may host avian and swine-origin influenza (pH1N1) virus co-infections, which generate reassortant viruses with high pathogenicity in mammals. Objectives We assessed the prevalence of avian and swine influenza viruses in US-based bird handlers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 20 publications
1
18
0
4
Order By: Relevance
“…A serosurvey conducted after the epizootic outbreak caused by (HPAI)H7N7 in the Netherlands in 2003 identified antibodies in approximately half of exposed individuals and household contacts of infected persons [5, 36]. H5N2 transmission has been reported from poultry and wild birds to humans in Japan and the United States, respectively, although no symptoms were recorded [37, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…A serosurvey conducted after the epizootic outbreak caused by (HPAI)H7N7 in the Netherlands in 2003 identified antibodies in approximately half of exposed individuals and household contacts of infected persons [5, 36]. H5N2 transmission has been reported from poultry and wild birds to humans in Japan and the United States, respectively, although no symptoms were recorded [37, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] eighteen articles assessed commercial poultry workers, seven articles assessed non-commercial poultry workers (i.e. backyard farmers), and four studies assessed other workers including bird banders, 18 handlers of migratory birds, 19 firefighters, 11 and government workers 11 involving in culling.…”
Section: Iv2 Phiwg Literature Reviewmentioning
confidence: 99%
“…Previous studies showed that people who are in frequent contact with infected animals can be infected by the H5N2 viruses (Ogata et al, 2008; Yamazaki et al, 2009; Shafir et al, 2012; Wu et al, 2014c). A large number of novel HPAI H5 virus infections have occurred in the human population and a lack of pre-existing immunity to H5 AIVs poses a potential public health risk.…”
Section: Introductionmentioning
confidence: 99%